2023
DOI: 10.1101/2023.04.04.535379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial analysis of human lung cancer reveals organized immune hubs enriched for stem-like CD8 T cells and associated with immunotherapy response

Abstract: The organization of immune cells in human tumors is not well understood. Immunogenic tumors harbor spatially-localized multicellular 'immunity hubs' defined by expression of the T cell-attracting chemokinesCXCL10/11and abundant T cells. Here, we examined immunity hubs in human pre-immunotherapy lung cancer specimens, and found that they were favorably associated with response to PD1-blockade. Immunity hubs were enriched for many interferon-stimulated genes, T cells in multiple differentiation states, andCXCL9/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Increased lymphocyte recruitment may be caused in part by enriched CXCL11-CXCR3 ligand-receptor interactions between myeloid and B/T cells in TP53 mut tumors, most notably exhausted T cells. We observed some overlap of the myeloid and T cell phenotypes in TP53 mut LUAD, the anti-tumor immunity hub we reported previously in colorectal cancer 97 , and the stem immunity hub in NSCLC 98 , but additionally report here B/Plasma cell tumor infiltration, T cell exhaustion (supported by an independent scRNA-seq validation compendium), and the enrichment of SPP1-expressing TAMs. Our findings of a potentially more immunogenic TME in TP53 mut LUAD is consistent with previous studies reporting higher levels of anti-tumor immune signatures 99 in TP53 mut vs. TP53 WT LUAD using bulk RNA-seq data from TCGA and longer survival in advanced TP53 mut vs. TP53 WT NSCLC patients receiving immune checkpoint therapy 100 .…”
Section: Discussionsupporting
confidence: 81%
“…Increased lymphocyte recruitment may be caused in part by enriched CXCL11-CXCR3 ligand-receptor interactions between myeloid and B/T cells in TP53 mut tumors, most notably exhausted T cells. We observed some overlap of the myeloid and T cell phenotypes in TP53 mut LUAD, the anti-tumor immunity hub we reported previously in colorectal cancer 97 , and the stem immunity hub in NSCLC 98 , but additionally report here B/Plasma cell tumor infiltration, T cell exhaustion (supported by an independent scRNA-seq validation compendium), and the enrichment of SPP1-expressing TAMs. Our findings of a potentially more immunogenic TME in TP53 mut LUAD is consistent with previous studies reporting higher levels of anti-tumor immune signatures 99 in TP53 mut vs. TP53 WT LUAD using bulk RNA-seq data from TCGA and longer survival in advanced TP53 mut vs. TP53 WT NSCLC patients receiving immune checkpoint therapy 100 .…”
Section: Discussionsupporting
confidence: 81%
“…Highly coordinated immune cell networks with enrichment of activated or cytotoxic T cells have recently been identified as key features associated with response to immunotherapy across a variety of cancer types, largely focused on solid tumor responses to immune checkpoint blockade (ICB). 88,[90][91][92][93] In these settings, communities of diverse immune cells, including T and B cells, often accompanied by antigen presenting cells, have been described to aggregate into tertiary lymphoid structures (TLS) or TLS-like neighborhoods, 94 which are thought to promote T-and B-cell anti-tumor memory and effector activity. [95][96][97][98][99][100][101][102] Multiple recent studies of the spatial relationships of immune cells in cancer have pointed toward stemlike CD8+ T cells expressing PD-1 and TCF-1/TCF-7 as a hub for anti-tumor immunity, often in complex with T helper and myeloid cell populations, such as dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97][98][99][100][101][102] Multiple recent studies of the spatial relationships of immune cells in cancer have pointed toward stemlike CD8+ T cells expressing PD-1 and TCF-1/TCF-7 as a hub for anti-tumor immunity, often in complex with T helper and myeloid cell populations, such as dendritic cells. 90,92,[103][104][105][106] For myeloid malignancies, however, such immune networks have been only minimally evaluated (for example, in the pediatric AML setting 107 ) in part due to the technical obstacles of applying high dimensional sequencing and spatial profiling approaches to marrow tissue that has been conventionally processed using harsh decalcification procedures, though advancing technologies and analytical methods may overcome this challenge. [108][109][110] The response of AML to immunotherapies such as ICB have been disappointing, 65,111 and defining the role of TLS-like structures or other cellular networks could serve to advance our understanding of the critical cellular players needed to coordinate an effective anti-leukemia response.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 22 , 25 Recent work has demonstrated that these stem-like cells frequently inhabit specific clusters of immune cells within tumors. 26 Moreover, it has been found that exhausted T-cells in tumors can often be traced back, or ‘clonally linked’, to these stem-like cells located in tumor draining lymph nodes. To our knowledge, the role of stem-like T-cells and radiotherapy’s effects on them in mediating the recent failures of immunotherapy combined concurrently with conventionally fractionated chemoradiation in HNSCC patients (i.e.…”
Section: Discussionmentioning
confidence: 99%